Trajectories of fertility intentions among women living with HIV in South Africa. Issue 2 (1st February 2021) - Rucinski, Katherine B.; Powers, Kimberly A.; Pettifor, Audrey E.; Black, Vivian; Pence, Brian W.; Chi, Benjamin H.; Rees, Helen; Schwartz, Sheree R.
ABSTRACT: Fertility intentions are thought to be dynamic among women of reproductive age, yet few studies have assessed fertility intentions over time among women with HIV. We examine temporal patterns of fertility intentions in women with HIV to assess the extent to which fertility intentions – and the corresponding need for safer conception and judicious antiretroviral therapy (ART) regimen selection – vary over time. 850 non-pregnant HIV-positive women aged 18–35 on or being initiated onto ART in Johannesburg, South Africa were enrolled into a prospective cohort study (2009–2010). Fertility intentions were assessed at enrollment and at 30-day intervals via an interviewer-administered questionnaire. We used group-based trajectory modelling to identify longitudinal patterns of fertility intentions over 12 months. We identified four patterns of fertility intentions, which we labelled "consistently low" (representing ∼60% of the population), "low and increasing" (∼23%), "high and increasing" (∼12%), and "high and decreasing" (∼5%). Our findings suggest that a single family-planning assessment at one time point is insufficient to fully identify and meet the reproductive needs of women with HIV. As HIV testing and treatment evolve in South Africa, routine screening for fertility intentions can offer important opportunities to optimize HIV treatment, prevention, and maternal and child health.